Validation of a Sunlight Availability Simulation Model - Man, Ar; Chaichana, Chatchawan; Rinchumphu, Damrongsak; Wicharuck, Suwimon; Wanison, Ramnarong (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Sunlight availability for plants plays an important role in determining whether a plant can produce its maximum productivity output. The study developed a Rhinoceros simulation model that can predict the sunlight availability received in the surface of interest on a vertical farming (VF) shelf design for a particular crop, given that the weather data of the location is known. The simulation model was developed and validated against the experiment. Moreover, the simulation model is compared against other research data from different countries. The dimensions of the experiments from Indonesia and Japan were replicated in the developed Rhinoceros simulation model, and the simulation results were compared against the experiment results. The analysis shows that the model can predict sunlight availability in a similar way to the research data of other studies.